Resposta :
[tex]a)( - 3) {}^{5} = ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) = \boxed{ - 243}[/tex]
______________________________________
[tex]b)( - 3) {}^{4} = ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) = \boxed{ + 81}[/tex]
______________________________________
[tex]c)( - 3) {}^{6} = ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) = \boxed{ + 729}[/tex]
______________________________________
[tex]d)( - 3) {}^{7} = ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) \times ( - 3) = \boxed{ - 2 \: 187}[/tex]
Alternativa correta Letra A
______________________________________